Introduction to agricultural economics (Pearson, 2015)
Introduction to Agricultural Economics, Sixth Edition, provides readers with a systematic introduction to the basic economic concepts and issues impacting the U.S. food and fiber industry and offers strong coverage of macroeconomic theory and international trade.